Androgen deprivation therapy in men with prostate cancer is not associated with COVID‐19 infection. Issue 6 (19th January 2023) - Davidsson, Sabina; Messing Eriksson, Anna; Udumyan, Ruzan; Swanholm, Per; Lewin Lundh, Maria; Widing, Carolina; Lindlöf, Christina; Fridfeldt, Jonna; Andersson, Sven‐Olof; Fall, Katja
Abstract: Background: Androgens may play a role in severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) infection and host responses as the virus is dependent on the androgen‐regulated protein transmembrane serine protease 2 for cell entry. Studies have indicated that prostate cancer patients receiving androgen deprivation therapy (ADT) are at reduced risk of SARS‐CoV‐2 infection and serious complications compared with patients without ADT, but data are inconsistent. Methods: A total of 655 prostate cancer patients who were under surveillance at two urology departments in Sweden on April 1, 2020 were included in the study as well as 240 patients with benign prostatic hyperplasia (BPH). At follow‐up early in 2021, the participants completed a questionnaire containing information about symptoms compatible with coronavirus disease 2019 (COVID‐19). Blood samples were also collected for the assessment of SARS‐CoV‐2 IgG antibodies (SARS‐CoV‐2 Total; Siemens). We used multivariable logistic regression models to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for the association between ADT and the risk of SARS‐CoV‐2 infection. Results: The cumulative incidence of SARS‐CoV‐2 seropositivity was 13.4% among patients receiving ADT and 10.4% among patients without ADT. After adjusting for potential confounders, we observed no differences in symptoms or risk of SARS‐CoV‐2 infection between patients with and without ADT (OR: 0.98; 95% CI: 0.52–1.85). Higher body mass index, Type 1 diabetes, and prostate cancer severity, defined by high Gleason score (8–10; OR: 2.06; 95% CI: 1.04–4.09) or elevated levels of prostate‐specific antigen (>20 µg/l; OR: 2.15; 95% CI: 1.13–4.07) were associated with increased risk of SARS‐CoV‐2 infection. Overall, the risk of SARS‐CoV‐2 infection was not higher among men with prostate cancer than among men with BPH. Conclusions: Our results do not support the hypothesis that ADT use in prostate cancer patients reduces the risk or symptom severity of SARS‐CoV‐2 infection or that prostate cancer patients are at increased risk of COVID‐19 compared with men without prostate cancer.